Pembinaan Sanggar Sastra di SD Negeri 76/IX Mendalo Darat Untuk Meningkatkan Kemampuan Apresiasi Sastra dan Kreatifitas Siswa - Wulandari, Sovia; Suryani, Irma; Wilyanti, Liza Septa; Triandana, Anggi; Resiyani, Wulan (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Learning about literary appreciation in elementary schools is an important lesson to increase students' creativity. The problem currently faced is that students' lack of interest in writing literature makes students not creative and productive. The problem of students' lack of interest at SD Negeri 76/IX Mendalo Darat in writing literature means that students are unable to take part in various creative writing competitions. One way to overcome this problem is by holding a literary studio at SD Negeri 76 Mendalo Darat as an extracurricular activity. The guidance provided uses methods of socialization, teaching, training and mentoring students in literary appreciation activities. The results obtained from this service activity are that students are skilled in receptive literary appreciation, namely reading literary works and some students are skilled in writing literature, and some are skilled in performing literature, such as telling stories, reading poetry, and playing drama. Literary works written by students are collected in the form of children's poetry anthologies and collections of children's stories.ABSTRAKPembelajaran apresiasi sastra di sekolah dasar merupakan pembelajaran yang penting untuk meningkatkan kreatifitas siswa. Permasalahan yang dihadapi sekarang ini yaitu kurangnya minat siswa dalam menulis sastra membuat siswa tidak kreatif dan produktif. Masalah kurangnya minat siswa SD Negeri 76/IX Mendalo Darat dalam menulis sastra membuat siswa tidak bisa mengikuti berbagai lomba tulisan kreatif. Salah satu cara untuk mengatasi masalah tersebut yaitu dengan mengadakan pembinaan sanggar sastra di SD Negeri 76 Mendalo Darat sebagai kegiatan ekstrakurikuler. Pembinaan yang diberikan menggunakan metode sosialisasi, pengajaran, pelatihan, dan pembimbingan siswa dalam kegiatan apresiasi sastra. Hasil yang diperoleh dari kegiatan pengabdian ini ialah siswa terampil dalam apresiasi sastra yang bersifat reseptif yaitu membaca karya sastra dan sebagian siswa terampil dalam menulis sastra, dan sebagian lagi terampil dalam mementaskan sastra, seperti berdongeng, membaca puisi, dan bermain drama. Karya sastra yang telah ditulis oleh siswa dikumpulkan dalam bentuk buku antologi puisi anak dan kumpulan cerita anak.